Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1093/nar/26.13.3286
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in NPS1/STH1, an essential gene encoding a component of a novel chromatin-remodeling complex RSC, alters the chromatin structure of Saccharomyces cerevisiae centromeres

Abstract: The NPS1/STH1 gene encodes a nuclear protein essential for the progression of G2/M phase in Saccharomyces cerevisiae . Nps1p shares homology to Snf2/Swi2p, a subunit of a protein complex known as the SNF/SWI complex. Recently, Nps1p was found to be a component of a protein complex termed RSC (3) essential for mitotic growth, whereas its function is unknown. We isolated a temperature-sensitive mutant allele of NPS1 , nps1-105, and found that the mutation increases the sensitivity to thiabendazole (TBZ). At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 58 publications
12
94
1
Order By: Relevance
“…RSC mutants arrest at the G 2 /M stage of the cell cycle (Cao et al 1997;Tsuchiya et al 1998;Angus-Hill et al 2001), but there is no significant overlap between RSC targets and genes involved in cell cycle control or the genes whose expression oscillates during the cell cycle. The few cell cycle-regulated genes that are bound by RSC are not biased toward any specific phase of the cell cycle.…”
Section: Rsc1 and Rsc2 Forms Of The Rsc Complex Associate With Commonmentioning
confidence: 99%
See 1 more Smart Citation
“…RSC mutants arrest at the G 2 /M stage of the cell cycle (Cao et al 1997;Tsuchiya et al 1998;Angus-Hill et al 2001), but there is no significant overlap between RSC targets and genes involved in cell cycle control or the genes whose expression oscillates during the cell cycle. The few cell cycle-regulated genes that are bound by RSC are not biased toward any specific phase of the cell cycle.…”
Section: Rsc1 and Rsc2 Forms Of The Rsc Complex Associate With Commonmentioning
confidence: 99%
“…Mutations in several RSC subunits show a typical G 2 /M arrest characterized by large budded cells containing 2N or 4N chromosomes (Cao et al 1997;Tsuchiya et al 1998;Angus-Hill et al 2001). The basis for this G 2 /M arrest is unknown, but it depends on the spindle body checkpoint.…”
mentioning
confidence: 99%
“…Our recent analysis of the function of Nps1p in the cell division cycle, using a temperature sensitive nps1-105 mutant, showed that this mutation causes an alteration in chromatin structure surrounding centromeres at 38 ЊC and leads to G2/M arrest, possibly through the spindle-assembly checkpoint control system (Tsuchiya et al 1998). In contrast to the mitotic cell division cycle, the nps1-105 mutation affected the expression of several early meiotic genes during the sporulation process.…”
Section: Discussionmentioning
confidence: 99%
“…We have isolated a temperature-sensitive (ts) mutant allele of NPS1, nps1-105, which carries a single base substitution within the open reading frame (ORF), G to A at position 2288, resulting in the amino acid substitution of cysteine to tyrosine at position 763 (Tsuchiya et al 1998). We verified that this mutant stopped growth at 38 ЊC with an accumulation of largebudded cells containing single nuclei of a 2C-DNA content.…”
Section: A Temperature Sensitive Mutation In Nps1 Reduces Sporulationmentioning
confidence: 92%
See 1 more Smart Citation